Demam Berdarah Dengue: Epidemiologi, Patogenesis, dan Faktor Risiko Penularan - Aryu Candra (Loka Litbang Kesehatan Pangandaran, 2010)
Dengue hemorrhagic fever is an infectious disease resulting spectrum of clinical manifestations that vary from the lightest, dengue fever, hemorrhagic fever and dengue fever are accompanied by shock or dengue shock syndrome. Its caused by dengue virus, transmitted by Aedes mosquitoes. The case is spread in the tropics, especially in Southeast Asia,Central America, America and the Caribbean, many causes of death in children 90% of them attacking children under 15 years old.Until now pathogenesis is unclear. There are two theories or hypotheses immunopatogenesis DHF and DSS is still controversial which secondary infections (secondary heterologus infection) and antibody-dependent enhancement. Risk factors for dengue transmission are rapid urban population growth, mobilization of the population because of improved transportation facilities and disrupted or weakened so that population control. Another risk factor is poverty which result in people not has the ability to provide a decent home and healthy, drinking water supply and proper waste disposal